Cardiac MRI assessment of anthracycline-induced cardiotoxicity - Mabudian, Leila; Jordan, Jennifer H.; Bottinor, Wendy; Hundley, W. Gregory (Frontiers in Cardiovascular Medicine, 2022)
The objective of this review article is to discuss how cardiovascular magnetic resonance (CMR) imaging measures left ventricular (LV) function, characterizes tissue, and identifies myocardial fibrosis in patients receiving anthracycline-based chemotherapy (Anth-bC). Specifically, CMR can measure LV ejection fraction (EF), volumes at end-diastole (LVEDV), and end-systole (LVESV), LV strain, and LV mass. Tissue characterization is accomplished through T1/T2-mapping, late gadolinium enhancement (LGE), and CMR perfusion imaging. Despite CMR’s accuracy and efficiency in collecting data about the myocardium, there are challenges that persist while monitoring a cardio-oncology patient undergoing Anth-bC, such as the presence of other cardiovascular risk factors and utility controversies. Furthermore, CMR can be a useful adjunct during cardiopulmonary exercise testing to pinpoint cardiovascular mediated exercise limitations, as well as to assess myocardial microcirculatory damage in patients undergoing Anth-bC.